Mass media coverage in Health & Oral Health-related advertisements: A content analysis in Kerala, India - Malliga Venkat; Chandrashekar Janakiram (Elsevier, 2021)
Background: In today's world, the mass media plays an important role, and it can provide a unified platform for all public health communication, comprehensive healthcare education, and guidelines. As a result, we investigated the various types of general health and oral health messages and advertisements broadcast through various forms of mass media. Objective: The main objective is to identify & analyze the health & oral-health related dialogue and messages with the content of the mass media. Method: ology: Content analysis of general health and oral health-related advertisements was done in various media, like the print media (magazines & newspapers), television (audio-visual) and radio stations (audio). The data was collected by an independent investigator, like prime time, advertisements, articles, and public service announcements (PSAs), etc., and the observations were recorded for subsequent analysis. Results: Only n ​= ​753 incidents of health n ​= ​663 (88.1%) and oral health n ​= ​90 (11.9%) were reported during the study period, out of 6180 pages of published print media and 200 ​h of prime-time broadcast channel & station advertisements, respectively. There are n ​= ​506 incidents in the print media, implying that health n ​= ​481 (95.1%) and oral health n ​= ​25 (4.9%) are, respectively. Compared to other media, audio-visual media, n ​= ​229, show 26.7% of incidents of oral health information (n 58), while 73.3% of incidents are of general health information (n 171). Only 38.9% of oral health incidents (n ​= ​7) were broadcast during prime time. Conclusion: The findings of this study may help promoters, policymakers, public health providers, and other stakeholders, to be more precise about general or oral health-related information to be effective in the messages the mass media have been utilizing and in improving future health.